1982
DOI: 10.1073/pnas.79.18.5445
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid sulfate sulfohydrolase (C2 sulfatase): the modulator of cellular levels of L-ascorbic acid in rainbow trout.

Abstract: The enzyme L-ascorbic acid 2-sulfate sulfohydrolase (C2 sulfatase) was purified from rainbow trout liver. The enzyme catalyzes the hydrolysis of L-ascorbic acid 2-sulfate and has a pH optimum at 6.0. It has a molecular weight of about 117,500 at pH 5.0 and is inhibited by a number of sulfhydryl blocking agents including L-ascorbic acid. C2 sulfatase activity was observed in most metabolic organs of rainbow trout. These findings suggest that the physiologic role of the enzyme is to maintain adequate cellular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 55 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…D-Isoascorbic acid also mimics the biological activity of ascorbic acid on fibroblasts in vitro (34). The antiscorbutic effects of ascorbic acid 2-0-sulfate and dehydroascorbic acid have been attributed to the existence of cellular systems or enzymes capable of converting them to ascorbic acid (31)(32)(33)(35)(36)(37). Thus, the activity of these compounds in our assay system is consistent with ascorbic acid being a specific effector of AcChoR increases on L5 cells.…”
Section: Methodssupporting
confidence: 76%
“…D-Isoascorbic acid also mimics the biological activity of ascorbic acid on fibroblasts in vitro (34). The antiscorbutic effects of ascorbic acid 2-0-sulfate and dehydroascorbic acid have been attributed to the existence of cellular systems or enzymes capable of converting them to ascorbic acid (31)(32)(33)(35)(36)(37). Thus, the activity of these compounds in our assay system is consistent with ascorbic acid being a specific effector of AcChoR increases on L5 cells.…”
Section: Methodssupporting
confidence: 76%
“…It has been suggested that AsA 2-sulphate is a storage form of AsA in rainbow trout (Halver et al, 1975) and that the enzyme AsA 2-sulphate sulfohydrolase modulates the cellular levels of AsA by its action on AsA 2-sulphate (Benitez & Halver, 1982). In the present study seasonal changes were found in the AsA 2-sulphate content of mullet brain and hepatic tissues, but the pattern of fluctuations differed from that of AsA and no clear relationship between the tissue levels of these two parameters was evident.…”
Section: Discussionmentioning
confidence: 99%
“…-ascorbyl-2-sulfate (C2S) is a heat-and oxidation-resistant compound which can be con-L verted into ascorbic acid by C2sulfatase in rainbow trout tissues (1). Efficacy of C2S as a vitamin C source for rainbow trout (Oncorhynchus mykiss) was reported in 1993 (2), but other reports questioned the efficacy of C2S (34).…”
Section: [Psebm 1994 Vol2061mentioning
confidence: 99%